UJARAN PANTANG DALAM MASYARAKAT DAYAK TAMAN KAPUAS ANALISIS ETNOGRAFI KOMUNIKASI - Apriyanti, Paskalia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract Taboo in the Dayak Taman Kapuas Â are all in the form of words which, if broken, will bring disaster that is still maintained today. This is the reason the researchers chose taboo in society Taman Dayak Kapuas using Ethnography of Communication.This study covers the classification of taboo, said component identification, and said underlying component smoothing taboo. The method used in this research is descriptive method with a form of qualitative research. Based on the analysis there are six classifications in taboo Â Dayak Taman Kapuas, which names parents, the name of a relative, the name of the deceased, names of people and animals, the name of the Lord, and certain words.Components of underlying smoothing taboo, the which for reasons of morals, strength dangerous, and and avoid the event or undesirable state. Â Keywords: Taboo, Taman Dayak Kapuas, Ethnography of Communication